Joint molecule resolution requires the redundant activities of MUS-81 and XPF-1 during Caenorhabditis elegans meiosis. - Nigel J O'Neil; Julie S Martin; Jillian L Youds; Jordan D Ward; Mark I R Petalcorin; Anne M Rose; Simon J Boulton (PLoS Genetics)
The generation and resolution of joint molecule recombination intermediates is required to ensure bipolar chromosome segregation during meiosis. During wild type meiosis in Caenorhabditis elegans, SPO-11-generated double stranded breaks are resolved to generate a single crossover per bivalent and the remaining recombination intermediates are resolved as noncrossovers. We discovered that early recombination intermediates are limited by the C. elegans BLM ortholog, HIM-6, and in the absence of HIM-6 by the structure specific endonuclease MUS-81. In the absence of both MUS-81 and HIM-6, recombination intermediates persist, leading to chromosome breakage at diakinesis and inviable embryos. MUS-81 has an additional role in resolving late recombination intermediates in C. elegans. mus-81 mutants exhibited reduced crossover recombination frequencies suggesting that MUS-81 is required to generate a subset of meiotic crossovers. Similarly, the Mus81-related endonuclease XPF-1 is also required for a subset of meiotic crossovers. Although C. elegans gen-1 mutants have no detectable meiotic defect either alone or in combination with him-6, mus-81 or xpf-1 mutations, mus-81;xpf-1 double mutants are synthetic lethal. While mus-81;xpf-1 double mutants are proficient for the processing of early recombination intermediates, they exhibit defects in the post-pachytene chromosome reorganization and the asymmetric disassembly of the synaptonemal complex, presumably triggered by crossovers or crossover precursors. Consistent with a defect in resolving late recombination intermediates, mus-81; xpf-1 diakinetic bivalents are aberrant with fine DNA bridges visible between two distinct DAPI staining bodies. We were able to suppress the aberrant bivalent phenotype by microinjection of activated human GEN1 protein, which can cleave Holliday junctions, suggesting that the DNA bridges in mus-81; xpf-1 diakinetic oocytes are unresolved Holliday junctions. We propose that the MUS-81 and XPF-1 endonucleases act redundantly to process late recombination intermediates to form crossovers during C. elegans meiosis.